2022
DOI: 10.2337/ds21-0094
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypoglycemia During Treatment of Hyperglycemic Crises

Abstract: Objective Diabetic ketoacidosis and hyperosmolar hyperglycemic state are life-threatening hyperglycemic crises often requiring intensive care unit (ICU) management. Treatment includes intravenous (IV) insulin with a transition to subcutaneous (SC) insulin upon resolution. Hypoglycemia is a common complication associated with treatment of hyperglycemic crises, but risk factors have not been well established. This study aimed to assess risk factors associated with hypoglycemia during treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The frequency of hypoglycemia during the IIITP (mean duration, 67 h) in our sample (present in about a quarter of patients) was proportionally similar to that observed in the first 48 h in previous studies (12–16%) [ 8 ]. Consistent with previous studies in patients hospitalized for hyperglycemic crises, hypoglycemia was more frequent in patients with low BMI [ 18 ], in patients with probable concomitant infection [ 21 ], and in those receiving higher doses of insulin [ 17 ]. Additional risk factors found in our study for hypoglycemia during HHC were older age, the presence of a greater number of comorbidities (higher CCI), and outpatient treatment with insulin prior to admission; these had not been reported in patients admitted for hyperosmolar crises, but had been documented in patients with diabetes who were admitted for other reasons [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The frequency of hypoglycemia during the IIITP (mean duration, 67 h) in our sample (present in about a quarter of patients) was proportionally similar to that observed in the first 48 h in previous studies (12–16%) [ 8 ]. Consistent with previous studies in patients hospitalized for hyperglycemic crises, hypoglycemia was more frequent in patients with low BMI [ 18 ], in patients with probable concomitant infection [ 21 ], and in those receiving higher doses of insulin [ 17 ]. Additional risk factors found in our study for hypoglycemia during HHC were older age, the presence of a greater number of comorbidities (higher CCI), and outpatient treatment with insulin prior to admission; these had not been reported in patients admitted for hyperosmolar crises, but had been documented in patients with diabetes who were admitted for other reasons [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown that the incidence of hypoglycemia during hyperglycemic crises depends on the dosage and amount of insulin received [ 13 20 ]. In addition, 2 studies performed in patients admitted for DKA demonstrated a higher incidence of hypoglycemia in patients with low body weight [ 18 ], fever [ 21 ], hepatic disease [ 21 ], and impaired renal function [ 18 , 21 ]. Thus, few studies have analyzed risk factors other than insulin therapy for the occurrence of hypoglycemia during the treatment of hyperglycemic crises.…”
Section: Introductionmentioning
confidence: 99%